PENGARUH PENDAPATAN USAHA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR LOGAM DAN SEJENISNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Laely Rahmawati; Kosasih Kosasih (Departemen Manajemen, 2020)
This study aims to find out operating revenue, operating costs, net profit, the effect of operating revenue on net profit, the effect of operating costs on net profit and the effect of operating revenue and operating costs on net profit of manufacturing companies metal and the like sub sector that listed on Indonesia Stock Exchange 2014-2018 period. The method used in this study is descriptive and verification with quantitative approach. 30 samples was obtained from the income statement of 6 companies per 2014-2018. Descriptive statistic, multiple linear regression analysis, coefficient of determination and hypothesis test is the statistics method used. From the results of this study note that operating revenue fluctuates and tends to increase, operating costs fluctuates and tends to increase, net profit fluctuates and tends to decreased, operating revenue is not influential to net profit, operating costs is influential to net profit, operating revenue and operating costs is simultaneously influential to net profit.